2008
DOI: 10.1007/s10822-008-9205-8
|View full text |Cite
|
Sign up to set email alerts
|

Neural network-based QSAR and insecticide discovery: spinetoram

Abstract: Improvements in the efficacy and spectrum of the spinosyns, novel fermentation derived insecticide, has long been a goal within Dow AgroSciences. As large and complex fermentation products identifying specific modifications to the spinosyns likely to result in improved activity was a difficult process, since most modifications decreased the activity. A variety of approaches were investigated to identify new synthetic directions for the spinosyn chemistry including several explorations of the quantitative struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0
15

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(90 citation statements)
references
References 16 publications
1
72
0
15
Order By: Relevance
“…88 In addition to intensive examination and analysis of the emerging SAR trends by traditional medicinal chemistry methods, a neural network-based quantitative SAR study was also applied to the database of existing compounds and their activities. [89][90][91] This application of artificial intelligence was used to help identify promising directions for further modifications of the spinosyn structure. Analysis of this artificial intelligence model suggested that O-alkyl groups on rhamnose that were longer than methyl would confer greater activity against tobacco budworm larvae and that lengthening the 3¢-O-methyl group in particular would be the most beneficial approach to study.…”
Section: Semisynthetic Derivatives and Sarmentioning
confidence: 99%
“…88 In addition to intensive examination and analysis of the emerging SAR trends by traditional medicinal chemistry methods, a neural network-based quantitative SAR study was also applied to the database of existing compounds and their activities. [89][90][91] This application of artificial intelligence was used to help identify promising directions for further modifications of the spinosyn structure. Analysis of this artificial intelligence model suggested that O-alkyl groups on rhamnose that were longer than methyl would confer greater activity against tobacco budworm larvae and that lengthening the 3¢-O-methyl group in particular would be the most beneficial approach to study.…”
Section: Semisynthetic Derivatives and Sarmentioning
confidence: 99%
“…1). Since the discovery of spinosad, a variety of naturally occurring spinosyns and semi-synthetic derivatives (spinosoids) have been identified, with many shown to have excellent insecticidal activity (e.g., Salgado and Sparks, 2005;Sparks et al, 2008). Recently, spinetoram (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, spinetoram (Fig. 1), a mixture of two syntheticallymodified spinosyns, was introduced as a new insect control agent with greater potency and faster speed of action relative to spinosad Sparks et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Many of these modifications on the naturally occurring spinosyns together with biological activities have been described previously (Crouse et al 1999 (10) with improved biological activity and improved spectrum of activity, especially against whiteflies (Crouse et al 2007;Sparks et al 2008). Spinetoram (10) is a mixture of two main components which can be prepared by alkylation of the mixture of the naturally occuring spinosyns J and L and subsequent hydrogenation.…”
Section: Semi-synthetic Analogues Of Spinosadmentioning
confidence: 99%